PENGARUH KONSELING KELUARGA DALAM MENINGKATKAN KESADARAN DAN MENGURANGI PERILAKU MEMBOLOS PADA SALAH SATU SISWA SMP DI KOTA BEKASI - Sevia Nuraeni; Arfina Syifa Salsabila; Hurriyyatun Kabbaro (CV. ADIBA AISHA AMIRA, 2025)
Truancy is one of the indicators of low student academic engagement. This study aims to explore the role of family counseling in raising awareness and reducing truancy behavior in a grade VIII student at a junior high school in Bekasi City. Using a qualitative approach through in-depth interviews with the Guidance Counseling Teacher (BK) and the student, this study identified various factors that influence the student's behavior, such as a broken home family background, authoritarian parenting patterns, and emotional instability. The results showed that the low fulfillment of the function of love in the family was one of the main causes of this problem. Through family counseling interventions, especially with the individual counseling stage by involving the role of the family in solving the counselee's problems, after counseling, there was an increase in family involvement, namely from the father and older sister to provide family support in motivating learning, increasing positive behavior, social skills. The research also emphasizes the importance of eight family functions, especially emotional support, as a foundation in shaping children's character and behavior. The approach used includes family counseling techniques to understand the role of the family as well as art therapy to help students express emotions non-verbally. The results of the analysis showed that family counseling succeeded in increasing family involvement, so that this had an effect on the positive behavior of the counselee as seen from the change in the counselee's attendance at school, who previously often skipped school to always attend and had positive communication development with the teacher if he was absent from school.